Evaluasi Pertumbuhan dan Perkembangan Arachis pintoi sebagai Biomulsa pada Budidaya Tanaman di Lahan Kering Tropis - Sumiahadi, Ade; Chozin, M. Achmad; Guntoro, dan Dwi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTCover crops is widely used as biomulch because of its advantages for land conservation, weed control and increasing soil nutrients, especially in upland agriculture. The objective of the research was to study the growth and development of Arachis pintoi as biomulch in upland agriculture. The experiment was carried out at IPB Experimental Field from February until May 2014. Observation was done everyweek up to 12 weeks with 10 plants were used for each observation. One stolon of A. pintoi with 4 internodes was planted in each 0.25 m2 plot. The results showed that root initiation of A. pintoi was occured at 3 weeks after planting (wap) and produced 42.4 roots with average root length of 17.10 cm on 12 wap.A. pintoi had nett assimilation rate of 0.0023 g cm-2 per day and relative growth rate of 0.052 g per day. With this growth rate, A. pintoi covered 58% of 0.25 m2 plot and produced biomass 10.08 g per plant within 12 wap. A. pintoi produced flowers on 4 wap and pods on 7 wap. A. pintoi produced root nodules through mutualism symbiosis with local Rhizobium. The equation for rate of coverage is Coverage (%) = 5.273 Time (wap)-16.512; 100% land coverage can be reached on 22 wap. Based on the results of this study, A. pintoi is potential to be used as biomulch; however, a denser spacing must be applied for faster land coverage.Keywords: land coverage, mulch, Rhizobium, stolon